Results of percutaneous coronary intervention for chronic total occlusions of coronary arteries: a single center report - Mustafa Çetin; Kayıhan Karaman; Cemil Zencir; Ünal Öztürk; Emrah Yıldız; Sami Özgül (KARE Publishing, 2013)
Objectives: Percutaneous coronary intervention (PCI) for chronic total occlusions (CTOs) is associated with lower rates of procedural success and higher complication rates compared with PCIs in non-CTO lesions. The purpose of this study was to analyze the relationship between lesion characteristics and procedural success rates and in-hospital outcomes after PCI for CTO with novel equipment. Study design: We evaluated the prospectively entered data of 63 consecutive patients undergoing PCI for CTO at our institute between August 2009 and June 2012. Results: A total of 63 patients (mean age: 64+-11, 71% male) with one CTO lesion each underwent PCI. There were 46 patients (mean age: 63+-10, 70% male) in the CTO success group and 17 patients (mean age: 65+-13, 76.5% male) in the CTO failure group. Successful revascularization was achieved in 73% of patients. We used antegrade approach in 61 cases and retrograde approach in 2 cases. Our predominant strategy was single-wire technique, which was used in 54 cases (85.7%), followed by parallel-wire technique in 7 cases (11.1%). Moderate-to-severe tortuosity (odds ratio [OR]: 9.732, 95% confidence interval [CI]: 1.783- 53.115, p=0.009) and occlusion duration (OR: 1.536, 95% CI: 1.178-2.001, p=0.002) were independent predictors of procedural failure in the multivariate analysis. No in-hospital major cardiac events occurred. Conclusion: We have reported a study with a relatively high success rate of PCI with very low procedural and in-hospital complications. Moderate-to-severe tortuosity was observed as the most challenging problem despite the utilisation of novel equipment and techniques for CTO recanalization.